(untitled) (Research, Society and Development, 2022)
This research aimed to know the diversity of palm species in the Amapá State. Data were obtained through consultation of national and international herbarium databases, visits to herbaria and field excursions. The botanical samples collected were identified by comparison with material from the Herbarium Amapaense (HAMAB), where it was incorporated, and from specialized bibliographies. Information on palm tree collections in Amapá is present in 11 herbaria, eight national and three internationals. Fifty species of palm trees were recorded, distributed in 15 genera, with 9 new occurrences for the State of Amapá. The genus with the highest number of species is Bactris Jacq. ex Scop. (15 spp.), followed by Geonoma Willd. (9 spp.), Astrocaryum G. Mey. (7 spp.) and Attalea Kunth (4 spp.). The most sampled municipalities are Pedra Branca do Amapari, Tartarugalzinho, Ferreira Gomes, Porto Grande and Macapá. HAMAB corresponds to the collection that has the largest number of samples. Knowledge of the diversity of palm trees will serve as a guide for carrying out new studies, as a source of consultation for the identification of palm species. Finally, this work points out the need for floristic-taxonomic studies, geographic distribution and reproductive biology, considering that there are areas with little or no collection.